Applying Dialysis Bags to Grow Microalgae and Measure Grazing Rates by Secondary Producers - Tian, Yang; Yi, Xiangqi; Gao, Kunshan (Frontiers in Physiology, 2022)
Traditional methods using sealed bottles to determine the grazing rates by secondary producers neglect chemical changes induced by biological activities during the incubation, giving rise to instable levels of nutrients, pH, pCO2, pO2 and other chemicals along with changing microalgal cell concentrations and grazers’ metabolism. Here, we used dialysis bags, which allows exchanges of nutrients and gases, to grow microalgae and to determine grazing rates of secondary producers. The specific growth rate of diatom within the dialysis bags increased with increasing water velocities, indicating its suitability to grow microalgae under dynamic water conditions. Then, we compared the grazing rates by the heterotrophic dinoflagellate Noctiluca scintillans measured with the traditional method using polycarbonate (PC) bottles and the approach with the dialysis bags, and found that these two methods gave rise to comparable grazing rates. Nevertheless, the concentrations of inorganic nitrogen and phosphate in the closed PC bottles were about 89–94% lower than those in the dialysis bags due to the microalga’s assimilation. Subsequently, we applied it to determine the grazing rates by a copepod and an oyster (in the presence of other grazers). Consistent results were obtained using the dialysis bags to determine grazing rates by copepods. During the mesocosm (3000 L) experiment in the presence of primary and secondary producers, the grazing rates by the oyster Crassostrea angulata were determined based on the difference of phytoplankton biomass within and outside of the dialysis bags that held all organisms in the mesocosm except the oyster. Since the dialysis bags are permeable to gases, the grazing rates by the oyster under 410 (AC) and 1,000 (HC) μatm CO2 were successfully measured, with a promising result that HC significantly increased the oyster’s grazing. We concluded that using dialysis bags to grow microalgae and to determine grazing rates is a reliable approach, especially under different levels of CO2 and O2.